2019
DOI: 10.1002/mbo3.948
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus niger upregulated glycerolipid metabolism and ethanol utilization pathway under ethanol stress

Abstract: Organic solvent-tolerant microbes play key roles in many industrial bioprocesses, such as biofuel production, biocatalysis, and bioremediation (Nicolaou, Gaida, & Papoutsakis, 2010). To obtain strains with tolerance to these solvents, an approach involves genetically engineering selected strains based on the knowledge of organic solvent-induced stresses and responses (Taylor, Tuffin, Burton, Eley,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Subsequently, hydrophobic metabolites were extracted separately for the intra- (cell pellet) and extracellular (supernatant) components using a 2:1 ( v / v ) mixture of chloroform to methanol. The concentrated extracts were then analyzed using the LC–MS-based untargeted metabolomics platforms [ 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, hydrophobic metabolites were extracted separately for the intra- (cell pellet) and extracellular (supernatant) components using a 2:1 ( v / v ) mixture of chloroform to methanol. The concentrated extracts were then analyzed using the LC–MS-based untargeted metabolomics platforms [ 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Next, the chemical structures of the altered metabolite ions were manually characterized using accurate masses, previously reported retention time [ 25 , 26 ], and tandem mass spectra (S1 Fig in S1 File ). Out of the 111 metabolite ions with changed levels, probable structures could be assigned to 83 ions or 75%, which is relatively high for untargeted metabolomics analyses (S1–S7 Tables in S1 File ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aspergillus niger resisted copper stress by converting sorbitol from glucose to produce a large amount of mannitol [ 27 ]. When Aspergillus niger was exposed to 5% ethanol stress, its growth amount was about 70% less than that under normal growth conditions [ 28 ]. Using untargeted metabolomics to study its reaction mechanism, it was found that TAG, DAG, and hTAGs significantly accumulated.…”
Section: Application Of Metabolomics In the Field Of Fungal Researchmentioning
confidence: 99%
“… ( A ) Pathway analysis overview depicting altered metabolic pathways in A. flavus from the 200-μg/mL CV-treated group and the control. ( B ) Biosynthesis of glycerolipids and phospholipids [ 35 ] in A. flavus [ 36 ]. The red boxes showed upregulated lipids of mycelium treated with 200-μg/mL CV vs. the control, the green boxes indicated downregulated lipids and the gray boxes were lipids undetected or not changed significantly in the pathways.…”
Section: Figurementioning
confidence: 99%